Study on Application of Membrane Technology in Treatment of Effluent from Dyeing Industries in Erode, TamilNadu - Prasanna, K; S.Anandh, K; Vimal Kumar, S; Edwin, A (International Journal of Engineering and Technology, 2018)
The textile dyeing industry is one of the hazardous polluting industries which uses water as the major source for their production and substantially the generation of wastewater leads to be a huge burden in treatment. The existing treatment methods adopted in most of the dyeing industries are said to be very old and its efficiency of removal is very less and at the same time it does not meet the standards for trade effluent discharge as prescribed by the regulatory boards. The study carried out on the application of Activated Carbon Filter (ACF) outlet in three stages of Reverse Osmosis results in reduction of 52% and the Total Dissolved Solids (TDS) is reduced to 226 ppm under the operation time of 10 hours. Significance reduction in pH, BOD, COD, TSS and Sulphates. The results say that the new technology of applying Nano-filtration and ultra-filtration will increase the efficiency of treatment. The effluent characteristics with the help this technology satisfy the standards. Â Â